1954
DOI: 10.1017/s0022172400027236
|View full text |Cite
|
Sign up to set email alerts
|

Human toxoplasma infection

Abstract: 1. By the dye test, toxoplasma antibodies in titres of 1/4 or more, were found in the sera of 25% of a sample of adult population of Sheffield.2. Significantly higher, when strength as well as number was considered, were the reactions of the sera of veterinary surgeons and abattoir workers.3. Still higher were the reactions of the sera of those who handled rabbits. Highest of all were those of rabbit trappers.4. Toxoplasma antibodies active to a titre of 1/40 in the dye test were found in 34% of wild rabbits a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

1957
1957
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 23 publications
1
31
0
Order By: Relevance
“…Munday (1969) also reported the isolation of T. gondii from 3 of 34 rabbits but did not present serological data for these rabbits. Beverley, Beattie & Roseman (1954), in a study of English wild rabbits, found 34 % to have a dye test titre of 1 in 40 and 5 % to have a titre of 1 in 160. However, Lainson (1955) failed to isolate T. gondii from 122 English wild rabbits.…”
Section: Immunofluorescencementioning
confidence: 97%
See 1 more Smart Citation
“…Munday (1969) also reported the isolation of T. gondii from 3 of 34 rabbits but did not present serological data for these rabbits. Beverley, Beattie & Roseman (1954), in a study of English wild rabbits, found 34 % to have a dye test titre of 1 in 40 and 5 % to have a titre of 1 in 160. However, Lainson (1955) failed to isolate T. gondii from 122 English wild rabbits.…”
Section: Immunofluorescencementioning
confidence: 97%
“…However, Lainson (1955) failed to isolate T. gondii from 122 English wild rabbits. He suggested that either the distribution of T. gondii in the wild was very localized or that the dye test titres reported by Beverley et al (1954) indicated 'experience' with Toxoplasma antigen rather than actual infection. Riemann et al (1978) stated that 'high antibody responses (indirect haemagglutination titres of 1 in 4016) are a result of recent, first-time exposure, chronic infection or repeated exposure to infection'.…”
Section: Immunofluorescencementioning
confidence: 99%
“…This may be demonstrated with the toxoplasmin skin test [558], which elicits delayed hypersensitivity. The large-scale use of the skin test, especially in population surveys, has yielded excellent agreement between the results of this test for delayed hypersensitivity and the presence or absence of antibody [558][559][560][561][562][563]. False-positive skin test results are rare [564].…”
Section: Tests Of Cell-mediated Immunitymentioning
confidence: 99%
“…A study in Sheffield revealed that positive dye-tests with higher fitres were more prevalent in trappers, abattoir workers, animal handlers and veterinarians than in the remainder of the population in the same region. 33 The trapped animals also had positive dye-tests. The fact that 20% of all female patients were sewing-machine operators in clothing factories could not be disregarded, and further questioning revealed that their workrooms had to be subjected to exterminatioii procedures regularly and rat-traps set.…”
Section: Skin-and Dye-tests * In Ocular Toxoplasmosismentioning
confidence: 99%